Remarks of One Who Remembers: Concerning Gurevich’s History of an Historian - Horská, Pavla (Dějiny – teorie – kritika, 2008)
Considering Istoriia istorika (The History of an Historian), the memoirs of the medievalist Aaron Yakovlevich Gurevich, the author discusses the genre of egohistoire in the second half of the twentieth century. She points out differences in approaches to historiographical research and society, using the examples of Gurevich’s memoirs and the memoirs of Jacques Le Goff, with whom the Russian medievalist had a positive relationship. Apart from Gurevich’s critical approach to the Soviet regime, she discusses the concessions he was compelled to make to it. She argues that a distinctive trait of Gurevich’s was his emphasis on the responsibility of the historian towards himself and, chiefly, towards the public.